GAYA KEPEMIMPINAN KEPALA MADRASAH DALAM MENINGKATKAN PROFESIONALITAS GURU MADRASAH TSANAWIYAH BAITURRAHIM KOLAKA - Kamarudin (UNISAN JURNAL, 2024)
This exploration expects to decide the authority style of Madrasah Heads in expanding the amazing skill of Madrasah Tsanawiyah Baiturrahim Kolaka Kabupaten Kolaka Mangolo Educators, Kolaka Rule, Southeast Sulawesi. Specialists utilize subjective exploration strategies. The essential information sources in this examination are the Madrasah Head, Educators and Understudies, while the auxiliary information sources come from madrasah organization reports. Information assortment strategies Specialists utilized perception, meetings and documentation. To approve the information, scientists utilized triangulation methods. From the clarification that has been done it very well may be reasoned that: 1). The Job of Madrasah Heads in Expanding Educator Amazing skill at Madrasah Tsanawiyah Baiturrahim Kolaka Kabupaten Kolaka HKSN, Mangolo Kolaka Regime, Southeast Sulawesi. The job of the Madrasah Head is to do his obligations with full liability fully intent on expanding educator impressive skill by adopting a regularizing strategy that can convince or rouse instructors to constantly work as indicated by their obligations. each, with ability in the field of study it covers; 2). The methodology and steps taken by the Madrasah Head in expanding the Impressive skill of Educators at Madrasah Tsanawiyah Babussalam, Mangolo Kolaka Rule, Southeast Sulawesi are via completing management utilizing a pondering, correspondence, arranging, coordination, assessment approach, with this execution in the end all points and targets will be understood, to further developing instructor execution; 3). Supporting and Repressing Elements The job of the Madrasah Head in Working on the Exhibition of Educators at Madrasah Tsanawiyah Babussalam, Mangolo Kolaka Rule, Southeast Sulawesi is to help all Madrasah Head programs, in particular inward and outside variables, offices and foundation, strategies and projects, the climate, etc. This can uphold movements of every kind to further develop educator execution and can likewise obstruct every arranged action, so there should be attention to all gatherings in doing their separate obligations well.